Deoxyribonuclease I inhibitors as potential neuroprotective agents - Marković, Ana; Šmelcerović, Andrija (Archives of Pharmacy, 2022)
Deoxyribonuclease I (DNase I), one of the best characterized mammalian endonucleases, breaks down both single-stranded and double-stranded DNA to produce 3’-OH/5’-P ends, with primarily dinucleotides, but also other oligonucleotides being the final products. DNase I is one of the major nucleases involved in DNA degradation during apoptosis, and therefore might have a crucial role in the development of many disease conditions caused by excessive cell death. Elevated DNase I levels and excessive apoptosis are associated with the development of numerous neurodegenerative disorders, including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, retinitis pigmentosa, spinal muscular atrophy, cerebellar degeneration... Thus, DNase I inhibitors represent an attractive potential target for the design of alternative strategies for the prevention and/or treatment of such neurodegenerative disorders. Inhibition of bovine pancreatic DNase I has been evaluated in vitro by a number of both monocyclic and polycyclic organic compounds, including furan, thiazole, benzocyclobutane, benzimidazole, thienopyrimidine and benzopyran derivatives. Among each group tested, there was at least one compound with better inhibitory properties against DNase I compared to crystal violet, used as a reference compound. The most potent DNase I inhibitors within the investigated compounds could be set as a good starting point for the development of new and more effective DNase I inhibitors with potential application in the prevention and/or treatment of neurodegenerative disorders. Moreover, due to the fact that there is no DNase I inhibitor defined as a "gold standard", these structures may represent new lead compounds in future trials.